Images that make childhood visible: photographic language in the childhood education - da Maia, Gilvana Menslin Oliveira; dos Santos, Genecilda (Pontifícia Universidade Católica de São Paulo, 2021)
With the advancement of technological resources and discussions around pedagogical documentation, photography has gained more and more space in the educational environment. It is common to see the dissemination of images of children in the educational environment in evaluations, websites of institutions and school murals. Thus, the problem of the present study was delimited: how can the photographic language give visibility to the actions of children in the instruments of communication with families? Qualitative research with documentary approach was defined as methodology. In the present study, narratives elaborated in 2019, using photographs, were analyzed by a teacher who works with 4-year-old children in the public school in the city of São José do Rio Preto. The data were categorized into two main axes: narratives from the investigative sessions and narratives from moments present in the routine. The data were analyzed from the perspective of the authors Salkeld (2014) and Lima (1995) on the photographic language. Regarding photography in education and pedagogical documentation Fochi (2019a) (2019b), Hoyuelos and Riera (2019) and Rinaldi (2014). The results of the documentary analyze point to the possibility of using photography, which is understood as a language and the record of the children’s investigation processes. It was observed in the analyzed instruments the presence of images that seek to highlight the children’s actions and thoughts, both in the moments proposed by sessions, as in the moments arising from children’s initiatives in everyday actions. Another point of analysis was written language, realizing the teacher’s concern with articulating the two languages, going beyond the description of images and using writing to inform and build narratives that value children’s actions in a dynamic in which image and text complement each other.